Probing massive black hole binary populations with LISA. Issue 2 (7th November 2019) - Katz, Michael L; Kelley, Luke Zoltan; Dosopoulou, Fani; Berry, Samantha; Blecha, Laura; Larson, Shane L
ABSTRACT: ESA and NASA are moving forward with plans to launch Laser Interferometer Space Antenna (LISA) around 2034. With data from the Illustris cosmological simulation, we provide analysis of LISA detection rates accompanied by characterization of the merging massive black hole (MBH) population. MBHs of total mass ${\sim}10^5\!-\!10^{10} \, M_\odot$ are the focus of this study. We evolve Illustris MBH mergers, which form at separations of the order of the simulation resolution (∼kpc scales), through coalescence with two different treatments for the binary MBH evolutionary process. The coalescence times of the population, as well as physical properties of the black holes, form a statistical basis for each evolutionary treatment. From these bases, we Monte Carlo synthesize many realizations of the merging MBH population to build mock LISA detection catalogues. We analyse how our MBH binary evolutionary models affect detection rates and the associated parameter distributions measured by LISA. With our models, we find MBH binary detection rates with LISA of ∼0.5–1 yr −1 for MBHs with masses greater than $10^5\, M_\odot$ . This should be treated as a lower limit primarily because our MBH hole sample does not include masses below $10^5\, M_\odot$, which may significantly add to the observed rate. We suggest reasons why we predict lower detection rates compared to much of the literature.